2019
DOI: 10.1039/c9cp00794f
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights into a non-heme 2-oxoglutarate-dependent ethylene-forming enzyme: selectivity of ethylene-formation versusl-Arg hydroxylation

Abstract: QM/MM calculations for a non-heme 2-oxoglutarate-dependent ethylene-forming enzyme reveal that the selectivity of ethylene formation versus succinate formation is determined by the relative energies of transition states for the competing CO2 insertion and O–O bond cleavage of the FeII-peroxysuccinate species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
92
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(119 citation statements)
references
References 77 publications
21
92
0
Order By: Relevance
“…The Fe-O distance has elongated to 1.796 Å and the axial Fe-N bond to 2.204 Å. These changes mimic previous calculations on analogous reaction mechanisms well [26][27][28][29][30][31][32][33][34][35][36]. The transition state has a modest imaginary frequency of i619 cm −1 , which is well lower than typical hydrogen atom abstraction transition states that usually have values well over i1000 cm −1 [72][73].…”
Section: Substrate Desaturation Via Pathways 1 Andsupporting
confidence: 76%
See 1 more Smart Citation
“…The Fe-O distance has elongated to 1.796 Å and the axial Fe-N bond to 2.204 Å. These changes mimic previous calculations on analogous reaction mechanisms well [26][27][28][29][30][31][32][33][34][35][36]. The transition state has a modest imaginary frequency of i619 cm −1 , which is well lower than typical hydrogen atom abstraction transition states that usually have values well over i1000 cm −1 [72][73].…”
Section: Substrate Desaturation Via Pathways 1 Andsupporting
confidence: 76%
“…For cysteine dioxygenase a combination of UV-Vis absorption and electron paramagnetic resonance studies implicated a short-lived oxygen-bound intermediate, which was tentatively identified as either the iron(III)-superoxo species or the bicyclic ring structure [24]. Many computational studies investigated the structure and properties of the iron(IV)-oxo species of nonheme iron dioxygenases in detail using either density functional theory model complexes or quantum mechanics/molecular mechanics methods [25][26][27][28][29][30][31][32][33][34][35][36]. These studies identified the iron(IV)-oxo as a quintet spin ground state showed it to be an efficient oxidant of substrate hydroxylation reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Optimized geometries of the triplet and quintet spin reactant complexes ( 3,5 Re) are shown in Figure 2. Similarly to previous computational studies on analogous iron(IV)-oxo complexes of nonheme iron enzymes [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84] and experimental EPR and Mössbauer measurements of related nonheme iron dioxygenases, 30,31,[85][86][87] the quintet spin state is the ground state. Because of this molecular orbital occupation, the Fe-O distance is short in 5 Re, i.e.…”
Section: Methodsmentioning
confidence: 80%
“…A recent computational study on EFE focused on the possible reaction pathways for the conversion of αKG into ethylene and three molecules of CO 2 and the alterative reaction mechanism for arginine hydroxylation . Thus, EFE binds a free arginine amino acid as a substrate into the binding pocket and with the help of dioxygen reacts αKG to ethylene, although a small amount of hydroxylated arginine is also observed .…”
Section: Second‐coordination Sphere Effects In Nonheme Iron Enzymesmentioning
confidence: 99%
“…Thus, EFE binds a free arginine amino acid as a substrate into the binding pocket and with the help of dioxygen reacts αKG to ethylene, although a small amount of hydroxylated arginine is also observed . Lai et al . used QM/MM on a full enzyme model of EFE and studied the full reaction mechanism for the two reaction pathways and established mechanisms leading to arginine hydroxylation and ethylene formation, and the key steps for the initial reaction steps are summarized in Scheme .…”
Section: Second‐coordination Sphere Effects In Nonheme Iron Enzymesmentioning
confidence: 99%